Ecological restoration of biocrusts in alpine tundra biomes - Letendre, Annie-Claude (Author); Coxson, Darwyn (Thesis advisor); Stewart, Katherine (Thesis advisor); University of Northern British Columbia (Degree granting institution); Sanborn, Paul (Committee member); Fraser, Lauchlan (Committee member) (University of Northern British Columbia, 2018)
Biocrusts are complex communities of bryophytes, algae, fungi, lichens, and cyanobacteria living at the uppermost surface of soils. They have a global distribution and commonly colonize early successional and newly disturbed habitats, where they play important functional roles by facilitating key ecosystem processes. While several studies have examined biocrust development and function in arctic and alpine environments, the potential to use biocrusts in the restoration of disturbed soils in alpine tundra biomes has rarely been examined. In a greenhouse trial, we evaluated the restoration of biocrust through artificial inoculation of soils with mature biocrust. Our results suggest that artificial inoculation with biocrusts increases soil surface nitrogen-fixation rates. In a field study, we characterized alpine biocrust communities from cool mesic and xeric environments and conducted an inoculation experiment to assess the recovery of biocrust structure and function. biocrust ecosystem alpine tundra biomes